Analisis SWOT dalam Merancang Strategi Pemasaran pada UKM Kue Bagea di Kota Palopo - Yuda Satria Nugraha; Nurjannah Nurjannah; Eka Febrianti; Anita Susanti; Didi Chandra Aditya (Yayasan Literasi Sains Indonesia, 2025)
The increasingly fierce competition in the culinary business requires business actors to develop appropriate marketing strategies in order to survive and thrive. This study aims to analyze the marketing strategies of Bagea Cake SMEs in Palopo City in increasing sales volume. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and questionnaires. A SWOT analysis was conducted to identify the strengths, weaknesses, opportunities, and threats they have. Based on the analysis results, Bagea Cake SMEs in Palopo City are in quadrant I, indicating that SMEs are classified as growing businesses and have a strong and promising position. The strategies that can be used are the Strength-Opportunity (SO) strategy or progressive (growth) strategy. Progressive strategies that can be applied to Bagea Cake SMEs in Palopo City include optimizing the quality of distinctive taste and attractive packaging to expand the market, maintaining customer loyalty and hygienic production processes to build a strong brand image, and using quality raw materials and brand identity as competitive advantages.